Mencari Makna Dalam Acara Mangupa-upa Di Kalangan Keluarga Etnik Toba - sitanggang, rades (Sekolah Tinggi Diakones HKBP, 2022)
The term “Mangupa-upa” means giving gifts or holding salvation. When the Mangupa-upa ceremony is held at the residence of a person or a family, there are relatives of the family, as well as friends. In this event held a banquet together, conversation, and then the delivery of gifts to someone or family who formulated. Mangupa-upa events are carried out in accordance with the context of life experienced by a person or a family which in essence can be grouped into two categories, namely the mangupa-upa event relating to the atmosphere of joy or the atmosphere of sorrow. The basic for doing the form of event-forma or also called mangupa tondi aims to provide reinforcement to someone, or a family who is formatted in the process of dealing with all kinds of threats that might endanger themselves. Vergouwen argues that the purpose of mangupa-upa is essentially to strengthen soul/tondi, increase the power residing within humans, and to strengthen the bond between humans and their homes.